2009
DOI: 10.1007/s12291-009-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid profile and antioxidant enzymes among south Indian men consuming coconut oil and sunflower oil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…There are only epidemiological data and small short-term interventions with the coconut oil and its association with CAD 16, 17, 18. Previous work from our institution showed that there were no differences in lipid profile (serum total cholesterol, triacylglycerols, and cholesterol in lipoprotein fractions) between persons taking coconut oil or sunflower oil 19 . Higher intake of coconut oil did not cause any significant increase in the concentration of lauric acid in blood among coconut oil consumers.…”
Section: Introductionmentioning
confidence: 52%
“…There are only epidemiological data and small short-term interventions with the coconut oil and its association with CAD 16, 17, 18. Previous work from our institution showed that there were no differences in lipid profile (serum total cholesterol, triacylglycerols, and cholesterol in lipoprotein fractions) between persons taking coconut oil or sunflower oil 19 . Higher intake of coconut oil did not cause any significant increase in the concentration of lauric acid in blood among coconut oil consumers.…”
Section: Introductionmentioning
confidence: 52%
“…Sabitha et al 26 conducted a cross-sectional study in 140 middle-aged Indian men with and without type 2 diabetes who self-reported typically consuming coconut oil or sunflower oil as 13% to 20% of their total energy intake over the past 6 years. Lipid profiles and oxidative stress parameters were compared between the groups and did not show any statistically significant differences between coconut oil and sunflower oil.…”
Section: Search Strategymentioning
confidence: 99%
“…Coconut oil contains approximately 90% saturated fats. Saturated fats are known to contribute to coronary artery disease (CAD) [15]. Coconut oil contains medium chain fatty acids such as lauric (C-12), caprylic (C-10) and myristic (C-14) acids.…”
Section: Introductionmentioning
confidence: 99%